Enhanced El Niño–Southern Oscillation Variability in Recent Decades. Issue 7 (4th April 2020) - Grothe, Pamela R.; Cobb, Kim M.; Liguori, Giovanni; Di Lorenzo, Emanuele; Capotondi, Antonietta; Lu, Yanbin; Cheng, Hai; Edwards, R. Lawrence; Southon, John R.; Santos, Guaciara M.; Deocampo, Daniel M.; Lynch‐Stieglitz, Jean; et al.
Abstract: The El Niño–Southern Oscillation (ENSO) represents the largest source of year‐to‐year global climate variability. While Earth system models suggest a range of possible shifts in ENSO properties under continued greenhouse gas forcing, many centuries of preindustrial climate data are required to detect a potential shift in the properties of recent ENSO extremes. Here we reconstruct the strength of ENSO variations over the last 7, 000 years with a new ensemble of fossil coral oxygen isotope records from the Line Islands, located in the central equatorial Pacific. The corals document a significant decrease in ENSO variance of ~20% from 3, 000 to 5, 000 years ago, coinciding with changes in spring/fall precessional insolation. We find that ENSO variability over the last five decades is ~25% stronger than during the preindustrial. Our results provide empirical support for recent climate model projections showing an intensification of ENSO extremes under greenhouse forcing. Plain Language Summary: Recent modeling studies suggest that El Niño will intensify due to greenhouse warming. Here new coral reconstructions of the El Niño–Southern Oscillation (ENSO) record sustained, significant changes in ENSO variability over the last 7, 000 years and imply that ENSO extremes of the last 50 years are significantly stronger than those of the preindustrial era in the central tropical Pacific. These records suggest that El Niño events already may be intensifying due to anthropogenic climate change. Key Points: Line Island corals provide 1, 751 years of monthly resolved ENSO variability from the mid‐Holocene to present ENSO strength is significantly weaker between 3, 000 and 5, 000 years ago compared to the 2, 000‐year periods both before and after ENSO extremes of the last 50 years are significantly stronger than those of the preindustrial era in the central tropical Pacific